EPR studies of V-ATPase with spin-labeled inhibitors DCC and Archazolid: interaction dynamics with proton translocating subunit c - Gölz, Jan Philipp; Bockelmann, Svenja; Mayer, Kerstin; Steinhoff, Heinz-Jürgen; Wieczorek, Helmut; Huss, Markus; Klare, Johann P.; Menche, Dirk (ChemMedChem, 2016)
Abstract Vacuolar-type H+-ATPases (V-ATPases) have gained recent attention as highly promising anticancer drug targets, and therefore detailed structural analyses and studies of inhibitor interactions are very important research objectives. Spin labeling of the V-ATPase holoenzyme from the tobacco hornworm Manduca sexta and V-ATPase in isolated yeast (Saccharomyces cerevisiae) vacuoles was accomplished by two novel methods involving the covalent binding of a (2,2,6,6-tetramethylpiperidin-1-yl)oxyl (TEMPO) derivative of N,N?-dicyclohexylcarbodiimide (DCC) to the essential glutamate residue in the active site and the noncovalent interaction of a radical analogue of the highly potent inhibitor archazolid, a natural product from myxobacteria. Both complexes were evaluated in detail by electron paramagnetic resonance (EPR) spectroscopic studies and double electron?electron resonance (DEER) measurements, revealing insight into the inhibitor binding mode, dynamics, and stoichiometry as well as into the structure of the central functional subunit?c of these medicinally important hetero-multimeric proton-translocating proteins. This study also demonstrates the usefulness of natural product derived spin labels as tools in medicinal chemistry.